2001
DOI: 10.2183/pjab.77.7
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter-level positioning on the seafloor

Abstract: Abstract:This Introduction. The space geodetic techniques have already been used in the monitoring of crustal deformations on land not only with high spatial and temporal resolutions but also with centimeter-level accuracy. In Japan, the continuous observation with the Global Positioning System (GPS) Earth Observation Network (GEONET) has been producing amazing results. These results have contributed significantly to the understanding of the complex crustal deformation processes.' The remote sensing from flyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 0 publications
0
46
0
Order By: Relevance
“…This technique has its origins in early work carried out by scientists at the Scripps Institution of Oceanography (Spiess, 1985). Our team at the Japan Coast Guard (JCG) and the Institute of Industrial Science, the University of Tokyo, has been developing this technique using a survey vessel and making repeated campaign observations along the major trenches (Asada and Yabuki, 2001;Mochizuki et al, 2003Mochizuki et al, , 2005Fujita et al, 2006a). Fujita et al (2006a) demonstrated that the repeatability of the position determination reaches an accuracy of a couple of centimeters under good conditions and proved the capability of detecting secular crustal movement at a seafloor reference point located off Miyagi Prefecture.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has its origins in early work carried out by scientists at the Scripps Institution of Oceanography (Spiess, 1985). Our team at the Japan Coast Guard (JCG) and the Institute of Industrial Science, the University of Tokyo, has been developing this technique using a survey vessel and making repeated campaign observations along the major trenches (Asada and Yabuki, 2001;Mochizuki et al, 2003Mochizuki et al, , 2005Fujita et al, 2006a). Fujita et al (2006a) demonstrated that the repeatability of the position determination reaches an accuracy of a couple of centimeters under good conditions and proved the capability of detecting secular crustal movement at a seafloor reference point located off Miyagi Prefecture.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, our team at the Hydrographic and Oceanographic Department of Japan (JHOD) and the Institute of Industrial Science, the University of Tokyo has been developing this technique using a survey vessel and making repeated campaign observations along the major trenches (Asada and Yabuki, 2001;Mochizuki et al, 2003Mochizuki et al, , 2005Fujita et al, 2006). Fujita et al (2006) have shown that the repeatability of the position determination reaches a couple of centimeters under good conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to detect seafloor movements with an accuracy of a few centimeters, GPS-acoustic combination technique has been developed (e.g., Spiess et al 1998;Asada and Yabuki, 2001). In Japan, our group first succeeded in detecting seafloor movements caused by interseismic plate convergence at the Japan Trench ) and has continued to monitor the movements including coseismic and postseismic deformation at the seafloor sites along the Japan Trench (e.g., Matsumoto et al 2006;Sato et al 2011a, b;Sato et al 2013b;Watanabe et al 2014) and the Nankai Trough (e.g., Yokota et al 2015).…”
Section: Methods and Observation Datamentioning
confidence: 99%